Rekonstruksi Limbah Makanan dalam Program Makan Gratis Nutrisi (MBG) Konsep Israf Perspektif di MTs Fathul Amin Matakali - Hapri, Fahmi; Fauziah; Nurliah; Irwandi; Rini (Li Falah: Journal of Islamic Economics and Business, 2026)
This study aims to analyze and reconstruct food waste behavior in the Free Nutritional Meal Program (MBG) based on the Islamic concept of israf. This study used a descriptive qualitative approach at MTs Fathul Amin Matakali. Data collection techniques included observation, interviews, and documentation. The results showed that food waste still occurs due to excessive food portions, student preferences for food, and low awareness of finishing food. From an israf perspective, this behavior is considered excessive, which is prohibited in Islam. Therefore, this study proposes reconstruction through Islamic-based consumption education, portion adjustments, and improvements to the food distribution system. This reconstruction is expected to reduce food waste and shape more responsible consumption behavior. Keywords :Food Waste, Israf, Free Nutritious Meal Program